P3_2_The Space Elevator - Boxley, Alex; Puchtler, Tim; Gray, Neil (Physics Special Topics, 2009)
This paper examines the feasibility for construction of a space elevator through simple physical analysis of a basic model. Beyond this consideration is made for further development of the model with the hope of ultimately creating a successful simulation which can be applied to a real future setting.